ANALISIS KEMAMPUAN LITERASI NUMERASI BERBASIS SOAL ASESMEN KOMPETENSI MINIMUM (AKM) BERDASARKAN TINGKAT KEMANDIRIAN BELAJAR SISWA KELAS V SD NEGERI 17 RANTAU - Mellania; Rosmaiyadi; Wasis Suprapto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Numeracy literacy ability is one of the important abilities for students to have. One of the factors that influence numeracy literacy ability is students' learning initiative and learning independence. This study aims to: 1) describe numeracy literacy ability based on AKM questions based on the level of learning independence of grade V students of SD Negeri 17 Rantau; 2) describe the factors that influence numeracy literacy ability based on AKM questions based on the learning independence of grade V students of SD Negeri 17 Rantau. The research method used is descriptive qualitative. The subjects of this study were 18 grade V students of SD Negeri 17 Rantau. The object of this study is numeracy literacy ability based on AKM questions based on the level of learning independence. Data collection techniques in this study used numeracy literacy ability tests, learning independence questionnaires, and interviews. The results of the study obtained were 1) numeracy literacy skills based on AKM questions based on the level of learning independence, namely, (a) students with a high learning independence category are quite capable of meeting the three indicators of numeracy literacy skills well, and have an average score of 69.25 with moderate criteria; (b) students with a moderate learning independence category are quite capable of meeting the three indicators of numeracy literacy skills well, and have an average score of 58.87 with moderate criteria; (c) students with a low learning independence category are only able to meet the first indicator, namely solving problems in the context of everyday life, but have not been able to analyze information, and have not been able to interpret the results of the analysis to make decisions well, and have an average score of 47.83 with low criteria. 2) factors that influence numeracy literacy skills based on AKM questions based on student learning independence are from the students themselves, including the level of learning motivation, interest, student intellectuality, independence, and concentration.